Effective Strategies for Teaching Listening Skills in TESOL - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
Listening is a crucial language skill that plays a vital role in the process of learning English. However, it is often underemphasized in TESOL classrooms. This article discusses effective strategies for teaching listening skills, focusing on the importance of comprehension, the role of listening in language acquisition, and various approaches to improve students' listening abilities. The article presents practical techniques that TESOL teachers can implement to enhance students' listening skills, thereby improving overall language proficiency.